From human antibody structure and function towards the design of a novel Plasmodium falciparum circumsporozoite protein malaria vaccine. (August 2018) - Wardemann, Hedda; Murugan, Rajagopal
Highlights: Characterization of protective natural human anti-PfCSP NANP antibodies. Potent human germline-encoded anti-PfCSP NANP antibodies. Identification of a non-protective B cell epitope in the PfCSP C-terminus. Protective B cell epitopes in the N-terminal junction. Abstract : Malaria is a life-threatening vector-borne disease caused by Plasmodium parasites that infect millions of people in endemic areas every year. The most advanced malaria vaccine candidate RTS, S targets the immune response against circumsporozoite protein of Plasmodium falciparum (PfCSP), the most deadly Plasmodium species in humans. PfCSP plays a fundamental role in parasite development as well as the establishment of the infection and is a molecular target of protective antibodies. However, RTS, S shows overall low efficacy and insufficient long-term protection. Therefore, a major goal in the development of an improved PfCSP-based vaccine remains the reliable and stable induction of protective and ideally sterilizing antibody titers. The molecular and functional characterization of human anti-PfCSP antibody responses paves the way for the rational design of novel immunogens for the development of an improved next-generation PfCSP malaria vaccine.